2010
DOI: 10.1002/eat.20862
|View full text |Cite
|
Sign up to set email alerts
|

Exercise interventions for women with anorexia nervosa: A review of the literature

Abstract: Few studies have systematically explored exercise as a part of treatment among patients with AN. Findings of the current review suggest a need for developing further research, but currently the field may benefit from standardized guidelines for treating excessive exercisers with AN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 28 publications
3
53
0
Order By: Relevance
“…Clinicians should thus consider using these "insider" recommendations from patients themselves for the management of activity during treatment. Our findings both support and extend the existing literature by corroborating theoretical claims with participant voices (Moola et al, 2013;Zunker et al, 2011). For instance, in addition to ensuring that the activity dose and outcome measures are specified, a nutritionally supported, graded, and progressive activity approach that includes psycho-education has been encouraged by researchers for the safe management of activity in AN (Calogero & Pedrotty, 2004;Moola et al, 2013).…”
Section: Recommendations and Conclusionsupporting
confidence: 82%
See 2 more Smart Citations
“…Clinicians should thus consider using these "insider" recommendations from patients themselves for the management of activity during treatment. Our findings both support and extend the existing literature by corroborating theoretical claims with participant voices (Moola et al, 2013;Zunker et al, 2011). For instance, in addition to ensuring that the activity dose and outcome measures are specified, a nutritionally supported, graded, and progressive activity approach that includes psycho-education has been encouraged by researchers for the safe management of activity in AN (Calogero & Pedrotty, 2004;Moola et al, 2013).…”
Section: Recommendations and Conclusionsupporting
confidence: 82%
“…Several research teams from many different countries, however, have questioned the prevailing wisdom that women with AN be restricted from activity (Hausenblas, Cook, & Chittester, 2008;Zunker, Mitchell, & Wonderlich, 2011). The results from several systematic reviews of literature demonstrate that nutritionally supported exercise interventions for patients with AN may improve several psychological parameters of health, such as quality of life and a sense of wellbeing.…”
Section: A Brief History On Anorexia and Exercisementioning
confidence: 99%
See 1 more Smart Citation
“…For example, several recent reviews have concluded that moderate amounts of exercise may be an effective therapy or adjunct to therapy for both ED Ng, Ng, & Wong, 2013;Wolff et al, 2011;Zschuckle, Gaudlitz, & Ströhle, 2013;Zunker, Mitchell, & Wonderlich, 2011) and other addictions (Fontes-Ribeiro, Marques, Pereira, Siva, & Macedo, 2011;Lynch et al, 2013). Moreover, exercise is also a widely recommended and accepted behavior that may foster a norm of inclusion to the larger healthy community as opposed to the stigmatization of being labeled with an addiction.…”
Section: Problematic Exercise and Eating Disorders Substance Use Dismentioning
confidence: 99%
“…Exercise plays an important role in the lives of many patients with AN (Davis & Fox, 1993;Michielli, Dunbar, & Kalinski, 1994;Ng, Ng, & Wong, 2013;Zunker et al, 2011). More than 50% of AN patients are engaged in physical activity.…”
Section: Exercise Physical Activity Sports and Gamesmentioning
confidence: 99%